Treatment of Septicaemic Cutaneous Ulcerative Disease in an Indian Flap Shell Turtle: A Case Report - Sab, Jafar; Kumar, Niteesh; Golasangi, Sateesh Ashok; Kanteppa, Praveen Madugonda; Gangaram Bijurkar, Rajeshwar (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Slowly but surely, turtles have become the pet of choice for many, rising to popularity in recent years. Septicaemic Cutaneous Ulcerative Disease (SCUD) or Shell rot is a critical issue in aquatic turtles and some reptiles caused by a bacterial or fungal infection. This may occur due to lack of knowledge of housing, i.e., keeping the turtles in dirty water or providing mouldy bedding and some environmental factors like high humidity and low temperatures are responsible for the occurrence of this disease (Lingayat et al., 2022). If proper measures for the control of shell rot are not taken, it can cause rot through the bone and into the body cavity (Khan et al., 2019). The Gram-negative bacteria that are normally present in the environment are the most common cause of bacterial infection (Kasim et al., 2017). Affected turtles show clinical signs such as presence of white spots on shell and hyperaemia in early stages of the disease, later cutaneous ulceration and fibrin deposit on the shell can be seen (Fowler and Miller, 2008; Jadhav et al., 2020). This documentation describes the successful treatment of septicaemic cutaneous ulcerative disease in an Indian flap shell turtle.